If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4u + -8 = 5(1 + -1u) Reorder the terms: -8 + 4u = 5(1 + -1u) -8 + 4u = (1 * 5 + -1u * 5) -8 + 4u = (5 + -5u) Solving -8 + 4u = 5 + -5u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '5u' to each side of the equation. -8 + 4u + 5u = 5 + -5u + 5u Combine like terms: 4u + 5u = 9u -8 + 9u = 5 + -5u + 5u Combine like terms: -5u + 5u = 0 -8 + 9u = 5 + 0 -8 + 9u = 5 Add '8' to each side of the equation. -8 + 8 + 9u = 5 + 8 Combine like terms: -8 + 8 = 0 0 + 9u = 5 + 8 9u = 5 + 8 Combine like terms: 5 + 8 = 13 9u = 13 Divide each side by '9'. u = 1.444444444 Simplifying u = 1.444444444
| x^4-8x^3+15x^2+4x=20 | | 4x-9x+50=2x+36 | | 15=-8+x | | 4(3x+5)-2(4x-3)= | | x^4-8x^3+15x^2+4x-20=0 | | 4.2=c/0.7 | | c-10=-22 | | 4a-16=a-5 | | 16-n/8=-6 | | -2x-9=11+3x | | 21x^2-18x-5=0 | | 7x+3=24+4x | | 8x^3+x^2-55x+42=0 | | x^5-3x^4+10=0 | | 2x^3-6x+3=0 | | -32-3x=5x-37 | | 2=x^2-8+5 | | 1+2x^2-x^4=0 | | 3x(x-5)=4x | | 3(a+2)=-5-2(a-3) | | w/7+9=-3 | | -3(3d-2)=4-d | | 12+5x=2x-11 | | 2x+x^2=224 | | 25=-n/6+(-19) | | 6(a-7)+10=4(a-7) | | 4(5-m)=3(3-2m) | | -8-(y+7)=-6y | | 22y=63 | | x^2+1+3x+6+x=180 | | 4r=2(r-5)-2 | | (x^2+6)(x^5-3x^3-54x)=0 |